Autism and α7-nicotinic acetylcholine receptors: new pharmacological and herbal interventions - Nourhan A. Khattab; Aya H. El-Kadem; Nada A. Ashour; Nageh Ahmed El-Mahdy; Nagla A. El-Shitany (Future Journal of Pharmaceutical Sciences)
Abstract Background Autism spectrum disorder (ASD) is a worldwide concern that affects 75 million people globally. ASD is characterized by neurological abnormalities that include impaired social interactions, stereotyped patterns of behavior, and cognitive difficulties. Numerous studies have focused on acetylcholine (ACh), which plays a significant role in modulating neuronal and immunological function via acting on muscarinic and nicotinic receptors. The α7-nicotinic acetylcholine receptors (α7nAChRs) are a key subtype of ACh receptors that directly activate to influence neuroprotective actions. Furthermore, it is a relatively recent hypothesis that α7nAChRs may indirectly influence neuronal behavior by regulating oxidative stress, inflammation, and apoptosis, which is becoming increasingly prevalent. Main text This review aims to provide a comprehensive overview of drugs and herbs promising to treat autism. Furthermore, great concern for the evidence suggesting that activation of α7nAChRs through some drugs or herbal medicine may impact brain function and clarify underlying molecular mechanisms, including oxidative stress, inflammation, and apoptosis. The review also discusses the challenges in targeting α7nAChR and its implications for medication development and prospective avenues for further investigation. Conclusion ASD is a substantial global issue due to the annual rise in case numbers; therefore, additional study is essential to identify effective therapeutic strategies targeting various pathways, including α7nAChRs.